2002
DOI: 10.1034/j.1600-0765.2002.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal distending toxin of Actinobacillus actinomycetemcomitans

Abstract: The cytolethal distending toxin (Cdt) of Actinobacillus actinomycetemcomitans, a periodontal pathogen, is a newly described cytotoxin with immunosuppressive properties, capable of causing cell cycle arrest of lymphocytes. The objectives of this study were to investigate the occurrence of A. actinomycetemcomitans with the cdt genotype in the subgingival plaque of periodontitis patients and to determine the association of this bacterial genotype with periodontal disease. A total of 146 subgingival plaque samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 24 publications
(26 reference statements)
3
39
1
1
Order By: Relevance
“…Ahmed et al (2001) found that 43 of 50 strains from periodontitis patients contained all three cdt genes and expressed CDT activity. In another study, PCR of subgingival plaque samples revealed that 13 of 106 diseased sites in 146 patients with aggressive and chronic periodontitis contained A. actinomycetemcomitans expressing all three cdt genes (Tan et al, 2002). Fabris et al (2002) reported that 39 of 40 A. actinomycetemcomitans isolates from a mix of healthy and periodontal diseased subjects expressed activity that caused the distension of CHO cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al (2001) found that 43 of 50 strains from periodontitis patients contained all three cdt genes and expressed CDT activity. In another study, PCR of subgingival plaque samples revealed that 13 of 106 diseased sites in 146 patients with aggressive and chronic periodontitis contained A. actinomycetemcomitans expressing all three cdt genes (Tan et al, 2002). Fabris et al (2002) reported that 39 of 40 A. actinomycetemcomitans isolates from a mix of healthy and periodontal diseased subjects expressed activity that caused the distension of CHO cells.…”
Section: Introductionmentioning
confidence: 99%
“…actinomycetemcomitans is the only oral bacterial species known to produce CDT (70). A number of studies collectively support that CDT may be important in the pathogenesis of aggressive periodontitis (1,19,64), although the actual contribution of CDT to this disease is not yet understood. In vitro studies have revealed that CDT stimulated receptor activator of NF-B ligand (RANKL) in human gingival fibroblasts (HGF) (9), which comprise the major cell population of the gingival connective tissue (5).…”
mentioning
confidence: 99%
“…Although there was some variation in toxin production among the strains, no clear relationship between CDT activity and periodontal status could be found. In another study A. actinomycetemcomitans was detected in 106/146 subgingival plaque samples isolated from periodontitis patients, and among these only 13 sites were positive for the cdt genotype (Tan et al 2002). However, 10 of these 13 positive sites were obtained from patients diagnosed with aggressive periodontitis, and the authors speculated that the cytotoxicity and immunosuppression by CDT may contribute to the pathogenesis of aggressive periodontitis (Tan et al 2002).…”
Section: Occurrence Of Cdts In Clinical Isolates From Various Geograpmentioning
confidence: 86%